Risks associated with tandem release of large and small ladybirds (Coleoptera: Coccinellidae) in heterospecific aphidophagous guilds. Issue 1 (23rd December 2013) - Omkar,; Mishra, Geetanjali; Kumar, Bhupendra; Singh, Neha; Pandey, Garima
Abstract: Multiple interactions occurring within aphidophagous guilds determine their final predation outcomes, i.e., antagonistic, additive, or synergistic. Based on these predatory outcomes, the suitability of guilds in suppressing aphid pests is determined. The present study assesses the efficacy of 11 guilds, formed from both larval and adult stages of four locally abundant aphidophagous coccinellids (Coleoptera: Coccinellidae), while exploiting the pea aphid, Acyrthosiphon pisum Harris (Hemiptera: Aphididae). The observed antagonistic effects within these guilds are resultants of enhanced predator–predator interactions due to the size and diversity of guild predators. Smaller ladybird predators maintained their usual body mass, probably by increasing their conversion efficiencies to compensate for their reduced prey consumption. However, larger ladybirds reported loss in their body mass, owing to their higher energy needs. The overall guild conversion efficiencies and growth rates were reduced. Among the experimental guilds, the observed prey mortalities were relatively higher in two-predator guilds, and within these two-predator combinations, the higher prey mortalities were recorded in those guilds where Coccinella septempunctata was one of the predators. Résumé: Les interactions multiples qui se produisent au sein des guildes d'aphidophages déterminent les résultats finaux de la prédation, par ex. antagonistes, additifs ou synergiques. Nous déterminons l'aptitude des guildes à éliminer les pucerons ravageurs d'après ces résultats de la prédation. Notre étude évalue l'efficacité de 11 guildes formées à la fois de stades larvaires et adultes de quatre coccinellidés (Coleoptera: Coccinellidae) aphidophages localement abondants qui exploitent le puceron du pois, Acyrthosiphon pisum Harris (Hemiptera: Aphididae). Les effets antagonistes observés au sein de ces guildes résultent d'interactions plus importantes entre prédateurs reliées à la taille et la diversité des guildes de prédateurs. Les coccinelles prédatrices de plus petite taille maintiennent leur masse corporelle habituelle, probablement en augmentant leurs rendements de conversion afin de compenser leur consommation réduite de proies. Cependant, les coccinelles plus grandes affichent une perte de masse corporelle à cause de leurs besoins énergétiques accrus. Les rendements de conversion globaux et les taux de croissance des guildes sont réduits. Parmi les guildes expérimentales, les mortalités observées chez les proies sont relativement plus élevées dans les guildes à deux prédateurs, et parmi ces guildes à deux prédateurs, les mortalités de proies plus élevées s'observent dans les guildes dont l'un des prédateurs est Coccinella septempunctata .